Effect of Oxytocin Injection into Umbilical Vein for Management of Retained Placenta - Shompa, Lima; Akhter, Sayeba; Nazneen, Khadija; Begum, Monnujan (Journal of Enam Medical College, 2014)
Background: Retained placenta is one of the causes of post-partum hemorrhage in Bangladesh as it is worldwide. If a retained placenta is left untreated, there is a high risk of maternal morbidity and mortality and it has inherent risks of infection and hemorrhage. Manual removal of placenta which is the recommended treatment of retained placenta usually requires regional or general anesthesia. Intraumbilical injection of saline solution with oxytocin might represent an important option for management of retained placenta. Objectives: The aim of this study was to assess the effect of intraumbilical vein oxytocin in the management of retained placenta and to compare it to the risk of manual removal of placenta. Materials and Methods: This experimental study was conducted in the department of Obstetrics and Gynecology in Dhaka Medical College & Hospital during July to December 2004. Total 50 patients with retained placenta were included in this study. The patients were divided purposively randomly into two groups - Groups A and B. Twenty patients in Group A were managed by intraumbilical vein injection of 10 units of oxytocin in 20 mL of normal saline slowly and 30 patients in Group B were managed by manual removal of placenta. Results: Among the patients of Group A, 16 (80%) delivered placenta spontaneously with expulsion time of 7-12 minutes. Remaining 4 patients (20%) required manual removal of placenta even after intraumbilical vein injection of oxytocin. Group A patients had less complications, required less blood transfusion, less antibiotics and less hospital stay compared to Group B patients. Conclusion: Intraumbilical vein administration of oxytocin is superior to manual removal in the management of retained placenta. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19678 J Enam Med Col 2014; 4(2): 102-105